Sampling and analysis of iron, steel and other ferrous metals. Methods of analysis. Multi-element methods. Determination of nickel, copper and cobalt contents by inductively coupled plasma atomic emission spectrometric method. Determination of cobalt content Part 3.40.4, (15th September 1997) - British Standards Institution,
No abstract available